ANALISIS PENGARUH KURS USD/AUD, SUKU BUNGA, HARGA MINYAK WEST TEXAS INTERMEDIATE, INDEKS ALL ORDINARIES DAN HARGA EMAS DUNIA TERHADAP RETURN SAHAM (Studi Kasus Sektor Mining & Resources Di Bursa Efek Australia (ASX) Periode 2001-2015) - Erwanto, Bonar; Haryanto, A. Mulyo (Faculty of Economics and Business Diponegoro University, 2016)
This study aims to determine the effect of the USD/AUD, interest rates, WTI oil prices, AORD index and NYMEX gold prices on stock returnsÂ of mining and resources in Australian capital market. Based on research defined by Nordin brothers and Ismail (2014) and supported by Rostamy, Hosseini and Bakhshitakanlou (2013) these factors are leading indicators that affect stock returns of mining and resources.This research is using non-random sampilng methodÂ for macroeconomic data in Australia, and it is analyzed with regression. Variable USD/AUD, interest rates, oil prices, AORD index and gold prices are partially and simultaniously analyzed regarding effect to the stock returns of mining and resources in Australian capital market.The results showed that in Australian capital market, the USD/AUD do not have effect with stock returns of mining and resources, interest rates do not have effect with stock returns of mining and it has negative effect with stock returns of resources, other variabels such as oil prices, AORD index and gold price have positive effect with stock returns of mining and resources. The results of this study, referred to the previous literature prove that the leading indicator of macroeconomic influence to cyclical stocks such as stock returns of mining and resources.